MPP UMP election successfully implemented in new norm - Nor Salwana, Mohammad Idris (2021)
PEKAN, 15 January 2021 - The Student Representative Council Election (PMPP), Universiti Malaysia Pahang (UMP) was successfully implemented in a new norm when the country was hit by the COVID-19 pandemic.